Internalisasi Kesenian Reog Ponorogo Dalam Menumbuhkan Karakter Disiplin Siswa Di SDN 2 Sumoroto Kauman Melalui Kegiatan Ekstrakurikuler: Internalisasi kesenian reog karakter disiplin - Yesi Yuana Oktavia; Muhammad Mahfud; Rahmat Rudianto (El-Miaz: Jurnal Pemikiran dan Pendidikan Dasar, 2023)
This research is motivated by a direction that can be implemented as a step to solve character problems, namely by internalizing character through the art of Reog Ponorogo. This type of research is a research stage carried out by collecting library sources, both primary and secondary. This research classifies data based on research formulas. This research is based on the consideration that the researcher intends to describe the internalization of Reog Ponorogo art in developing student characteristics at SDN 2 Sumurato Kauman through extracurricular activities. The research results show that students still behave and speak not in accordance with good ethics. Reog Ponorogo art extracurricular activities can develop the character of students at SD Negeri 2 Sumoroto, one of the attitudes that can be seen is the change in attitude that occurs in students who initially had an impolite attitude, often said dirty words to fellow friends, lack of student motivation towards Reog Ponorogo art, students who still use language as they please, lack manners and are difficult to manage. After participating in the Reog Ponorogo art activity, students changed for the better. The disciplined character of the students here are students who are obedient and willing to take part in Reog Ponorogo arts extracurricular activities without any coercion from anyone. Student discipline is carried out, namely that students never give up when taking part in extracurricular activities at school, are never late for extracurricular activities, always obey the rules.